Family Structure, Fertility and Child Quality in Colombia - Rocio Ribero (Yale University, Economic Growth Center, 2000)
This paper analyzes how family structure and fertility alter children quality in Colombia. Reduced form models to determine marital status of women and number of children ever born are estimated considering factors that affect women's bargaining powers inside the marriage. Tentative estimates of structural interdependence between these variables and children outcomes are outlined, revealing that marriage has a positive link with child quality and fertility has a negative link with child quality. Colombian national household survey data at rural and urban levels are used for the estimations.
Keywords: J00; J12; J13; 330; Family structure; fertility; child quality; Familie; Fertilität; Familienökonomik; Kolumbien